Effectiveness of doxycycline/ivermectin therapy for heartworm disease in regards to Wolbachia status in dogs - Spasojević Kosić, L; Lalošević, V; Kozoderović, G; Vračar, V; Simin, S; Potkonjak, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Heartworm disease (HWD), a highly important canine disease in veterinary medicine, is caused by Dirofilaria immitis (D. immitis). A therapeutic approach (the standard treatment or an alternative one, or even surgical intervention) in dogs naturally infected with D. immitis should be individually adjusted. The goal of this research was to test the effectiveness of an alternative therapeutic protocol for D.immitis and Wolbachia in 30 naturally infected dogs. Clinical and parasitological examinations (modified Knott test and SNAP Test IDEXX) were used for diagnosing Dirofilaria spp. Blood and urine laboratory, and radiographic examinations were used for the determination of HWD classes. An alternative therapy consisted of oral doxycycline and ivermectin administrations until microfilaremic and antigenic negativization, and was not longer than 9 months. Polymerase chain reaction (PCR) for wsp and 16S rRNA genes at the beginning and at the end of the therapy in 15 dogs was used for Wolbachia detection. The effectiveness of the alternative therapy for D. immitis and Wolbachia was 83.33% and 75% respectively. Neither the number of cured dogs nor the duration of the alternative therapy depended on the presence of Wolbachia. Thus, the alternative therapy with doxycycline and ivermectin is not based solely on targeting Wolbachia.